Lung and extrathoracic cancer incidence among underground uranium miners exposed to radon progeny in the Příbram region of the Czech Republic: a case–cohort study. Issue 2 (20th August 2021) - Kelly-Reif, Kaitlin; Sandler, Dale P; Shore, David; Schubauer-Berigan, Mary; Troester, Melissa; Nylander-French, Leena; Richardson, David B
Abstract : Objectives: Radon is carcinogenic, but more studies are needed to understand relationships with lung cancer and extrathoracic cancers at low exposures. There are few studies evaluating associations with cancer incidence or assessing the modifying effects of smoking. Methods: We conducted a case–cohort study with 16 434 underground uranium miners in the Czech Republic with cancer incidence follow-up 1977–1996. Associations between radon exposure and lung cancer, and extrathoracic cancer, were estimated with linear excess relative rate (ERR) models. We examined potential modifying effects of smoking, time since exposure and exposure rate. Results: Under a simple ERR model, assuming a 5-year exposure lag, the estimated ERR of lung cancer per 100 working level months (WLM) was 0.54 (95% CI 0.33 to 0.83) and the estimated ERR of extrathoracic cancer per 100 WLM was 0.07 (95% CI −0.17 to 0.72). Most lung cancer cases were observed among smokers (82%), and the estimated ERR of lung cancer per 100 WLM was larger among smokers (ERR/100 WLM=1.35; 95% CI 0.84 to 2.15) than among never smokers (ERR/100 WLM=0.12; 95% CI −0.05 to 0.49). Among smokers, the estimated ERR of lung cancer per 100 WLM decreased with time since exposure from 3.07 (95% CI −0.04 to 10.32) in the period 5–14 years after exposure to 1.05 (95% CI 0.49 to 1.87) in the period 25+ years after exposure. Conclusions: We observed positive associations between cumulative radon exposure and lung cancer, consistent with prior studies. We observed a positive association between cumulative radon exposure and extrathoracic cancers, although the estimates were small. There was evidence that the association between radon and lung cancer was modified by smoking in a multiplicative or super-multiplicative fashion.